Perceptions of Malaysian corporate customers towards Islamic banking products & services - Ahmad, Norafifah; Haron, Sudin (International Institute of Islamic Business and Finance, 2002)
Islamic banking system was established in Malaysia since 1983. To date, Islamic banking products are available at two full pledged Islamic banks and at all commercial and merchant banks in Malaysia. However, these products are still not fully accepted by customers. At the end of 2000, total deposit at conventional banks was RM381 billion while total deposit in Islamic system was RM31 billion. In the case of loans, RM416 billion was extended by conventional system, and RM21 billion was given by Islamic system. Since corporate customers are the key players in the economy, it is imperative that the reasons for them to choose or not to choose Islamic system be studied.This seminal study explores the perceptions of persons responsible in financial affairs of public listed companies in Malaysia. Among issues covered in this study were usage of conventional and Islamic banking facilities, respondents’ understanding of Islamic banking system, and their personal opinion on various aspects of Islamic banking products.